The Role of Organizational Management in Improving Para Badminton Achievement National Paralympic Committee Indonesia Purwakarta - Walidiandri, Pantar; Nurrachmad, Limpad (Universitas Majalengka, 2024)
The importance of sports in improving the quality of life and athlete performance for people with disabilities. The NPCI (National Paralympic Committee Indonesia) of Purwakarta Regency has shown its commitment to providing exemplary services for people with disabilities, including by developing disability sports such as badminton. Although the NPCI badminton team in Purwakarta Regency has achieved good results at the regional level, there are still obstacles, such as suboptimal facility management, unmet sports equipment needs, and ineffective management. This study aims to analyze the role of organizational management in improving the performance of para-badminton sports at the National Paralympic Committee Indonesia (NPCI) of Purwakarta Regency. The research method applied in this study is a qualitative approach with data collection through observation and structured interviews to gather data from six individuals and analyze organizational management aspects such as planning, organizing, actuating, and controlling. This research uses Millies and Huberman model analysis, which consists of four components that work synergistically: data collection, data reduction, display data, and conclusions drawn. The findings of this study show the effectiveness of organizational management in supporting the development of para-badminton athletes, especially in structured planning, efficient organizing, dynamic program implementation, and proactive control. Organizational management is essential in achieving optimal performance in para-badminton sports by improving athlete development programs and sports management concepts. The NPCI of Purwakarta Regency can improve its strategies and programs to achieve better performance in para-badminton sports and enrich the theoretical understanding of organizational management's role in para-sports.